Efeitos cardiovasculares das alatensinas (Des[Asp1]-[Ala1]-Angiotensinas) - Giovanni Naves Canta (2018)
Background and aim: Over the years new peptides, enzymes and receptors were described as components of the renin-angiotensin system (RAS). Currently, a new axis, composed by alatensins, a term suggested by the researcher Robson Augusto S. dos Santos, has been accepted and added to the RAS. This new family of peptides presents a Des[Asp1]-[Ala1]-Angiotensins structure. Therefore, the sequence of these peptides differs from the sequence of the peptides of the classical axis of the RAS in only an amino acid residue at the N-terminal: a Ala1 residue instead a Asp1 residue. In 2007 and 2013, studies described two new vasoactive peptides in the human plasma named angiotensin A (Ang A) and alamandine, respectively. Recent studies have shown that Ang A seems to have a vasoconstrictive effect through AT1 receptor while alamandine normally shows opposite effects through its receptor MrgD. Although the knowledge about the biological actions of these peptides in physiological and pathophysiological conditions has expanded in the last years, it is still limited. In this study, we evaluated the cardiovascular effects of the intravenous (i.v.) injections of alatensins [Ala1-Ang I, Ala1-Ang-(I-9), Ang A and alamandine] in normotensive animals. Methods: To perform this study, we used 12 weeks old Sprague-Dawley (SD) rats. To assess the cardiovascular parameters in vivo and to inject drugs, we cannulated the femoral artery and vein respectively, which was followed by an invasive assessment of arterial pressure (AP) through a pressure transducer coupled to data acquisition system (Biopac®, USA). To evaluate the effects of these peptides on vascular relaxation, vascular reactivity technique was used. Results: The i.v. injection of Ala1Ang I produced a dose-dependent pressor effect which was abolished by Captopril, inhibitor of the angiotensin converting enzyme (ACE). These results suggest that the observed effect is related to the formation of Ang A. Beside that, the potentiation of the peptide’s pressor effect with Dpro7, MrgD receptor antagonist, suggest that Ala1-Ang I is also a substrate for the formation of alamandine. The i.v. injection of Ang A, induced as expected an dose-dependent increase in AP. Interestingly, D-pro7 administration increased the duration of the effect, suggesting the formation of alamandine from the metabolism of Ang A. Ala1-Ang-(1-9) produced a dose-dependent vascular relaxation at aortic rings from SD rats. However, unlike the ex-vivo observed results, i.v. injection of Ala1-Ang-(1-9) did not induce important changes on the AP of SD rats. On the other hand, Ala1-Ang-(1-9) administration with Losartan, AT1 receptor antagonist, decreasedthe AP, while the administration of the peptide with Losartan and D-pro7 abolished the depressor effect, which indicated the formation of alamandine from Ala1-Ang-(1-9). Alamandine, the last peptide of this enzymatic route, presented a U-shaped curve effect on AP of SD rats, i.e., the intermediate doses of alamandine decreased more the AP than the lower and higher doses of the peptide, being the 0.02 ng dose that induced the greater reduction on AP. The depressor effect caused by the i.v. injection of alamandine was abolished by D-pro7, confirming alamandine as an endogenous ligand of the MrgD receptor. Moreover, the pre-treatment of SD rats with Losartan potentiated the depressor effect observed with the i.v. injection of alamandine, suggesting that AT1 receptor is involved in the observed results. Conclusion: This study demonstrated that peptides of the alatensins axis of the RAS are biologically active and the metabolism of these peptides leads, directly or indirectly, to the formation of alamandine.